2010
DOI: 10.3109/13625187.2010.504313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a monophasic combined oral contraceptive containing nomegestrol acetate and 17β-oestradiol on ovarian function in comparison to a monophasic combined oral contraceptive containing drospirenone and ethinylestradiol

Abstract: NOMAC/E2 achieves consistent ovulation inhibition, with suppressive effects on the ovaries at least similar to those of DRSP/EE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
2
33
0
1
Order By: Relevance
“…Therefore only women who had not used hormonal contraception for at least 3 months were included in the study and there was a 3-cycle run-in period with COC use alone prior to the DHEA/placebo treatment period. The observed qualitative changes of the (precursor) androgens and SHBG after COC use alone are in agreement with previous studies [1,2,[17][18][19][20][21], but the quantitative suppression of total T and free T by 62% and 86%, respectively is more pronounced than reported in the literature previously (mean of 31% and 61%, respectively) [1]. Importantly, all COC users experienced a decrease of their total and free T.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore only women who had not used hormonal contraception for at least 3 months were included in the study and there was a 3-cycle run-in period with COC use alone prior to the DHEA/placebo treatment period. The observed qualitative changes of the (precursor) androgens and SHBG after COC use alone are in agreement with previous studies [1,2,[17][18][19][20][21], but the quantitative suppression of total T and free T by 62% and 86%, respectively is more pronounced than reported in the literature previously (mean of 31% and 61%, respectively) [1]. Importantly, all COC users experienced a decrease of their total and free T.…”
Section: Discussionsupporting
confidence: 77%
“…Ovulation returned in both groups at an average of 3 weeks after last pill intake. In addition, an increase of 50 --60% in SHBG was found in users of the NOMAC--17b-E 2 COC, significantly less than the increase found in users of the DRSP--EE combination (300%) and significantly greater than that found with LNG--EE (36%) [55].…”
Section: Combined Oral Contraceptivesmentioning
confidence: 89%
“…A product containing estradiol and nomegestrol acetate as the progestin is approved for use in Europe but not the US. It has been shown to achieve effective ovulation inhibition, comparable to other pills on the market (11). Additionally, clinical trials of estetrol (E4) combined with drospironone or levonorgestrel have shown promise, although the amount of E4 is quite high (15 mg) (12).…”
Section: Female Hormonal Contraceptionmentioning
confidence: 99%